ASUHAN KEPERAWATAN PADA WANITA DEWASA DENGAN DIAGNOSA ASMA BRONKIAL - shanti dafris (Akper Kesdam I/Bukit Barisan Padang, 2019)
Asthma is an obstructive airway disease that is frightened by a narrowing of the airway. The narrowing of the airway will cause the client to experience dyspnoea, cough, and wheezing. The aim of the Literature Study is to explore the management of nursing care in patients with bronchial asthma in adult women. This type is qualitative research with Stdy Literartue, data collection is carried out by the data research method used in the literary study is the data used comes from the results of research conducted internationally. In searching for research journals published on the internet using Google, Academia, and scholar. with keywords: Nursing journals, research methods study literature Nursing with Bronchial Asthma. Analyzing data. Research journals in accordance with the inclusion criteria are then collected and a journal summary is made including the name of the researcher, the year of publication of the journal, study design, research objectives, samples, instruments (measuring instruments) and a summary of the results and findings. The summary of the research journals is entered into a table sorted according to the alphabet and year of publication of the journal and according to the format mentioned above. Research ethics used in the study of literature is taking a guaranteed validity study of literature, relevant to the research that will be carried out, being able to solve problems, studying literature that has been published, made in book form. The results of the assessment are usually shortness of breath, cough with phlegm, the general condition of the client is weak and, RR: 28 x / minute, S: 37oC. Diagnosis that appears ineffective diagnosis of airway clearance associated with increased secretion production, namely mucus and bronchospasm. The conclusion of this study is that after nursing care, the diagnosis can be resolved. Hope in the future to be able to maximize nursing actions so as to provide nursing care so as to provide optimal nursing care for patients with bronchial asthma.